Evaluación de la Cadena de Suministro del Café en la Provincia de Lengupá Bajo el Modelo SCOR (2022)
The purpose of this document is to evaluate the coffee supply chain in the province of Lengupá, it is based on the SCOR model, which is why the methodology established in this study is descriptive of an exploratory type with a mixed approach, it is considered descriptive by the identification of the supply chain associated with the production of coffee in the province of Lengupá, exploratory because there are particular problems of the region in the study and the innovation developed in the analysis method shows that it has not been applied before in this region, As a result of this project, the current conditions of the supply chain are based and it is valued in its different phases through metrics of the SCOR model. In the same way, the prioritization of problems shows that there are structural conditions in aspects such as infrastructure, costs, assets, agility, trust and sensitivity of processes within the chain to which represent the logistics level of this chain in the region. As a conclusion of this project, the processes of the chain are identified, highlighting the importance of characterizing the problem and proposing short-term alternatives; the metrics through which the processes, categories and integration links were prioritized emerge the performance of the supply chain for small coffee growers. In this same sense, the particular scenarios of the province of Lengupá require logistical integration and the intervention components are associated with various actors with differentiated roles within the chain